Stimulation of hair growth by Tianma Gouteng decoction: Identifying mechanisms based on chemical analysis, systems biology approach, and experimental evaluation - Zhang, Yanyan; Zhang, Shiqian; Long, Yunluan; Wang, Wuji; Du, Fanpan; Li, Jingjie; Jin, Feng; Li, Zheng (Frontiers in Pharmacology, 2022)
Hair serves important physiological functions, including temperature regulation and scalp protection. However, excessive shedding not only impacts these functions but can also significantly affect mental health and quality of life. Tianma Gouteng decoction (TGD) is a traditional Chinese medicine used for the treatment of various conditions, including hair loss. However, the associated mechanism underlying its anti-alopecia effect remains unknown. Therefore, this study aims to elucidate these mechanisms by employing systematic biology approaches, as well as in vitro and in vivo experimental validation. The chemical constituents of TGD were identified using UHPLC-MS/MS, from which 39 potential bioactive components were screened, while an additional 131 putative TGD beneﬁcial components were extracted from the Traditional Chinese Medicine Database and Analysis Platform (TCMSP) database. We then applied a two-dimensional network pharmacology approach to analyze the data, followed by validation studies combining molecular docking techniques with in vivo and in vitro experiments. From the 39 bioactive components, including quercetin, luteolin, fisetin, wogonin, oroxylin A, boldine, tetrahydroalstonine, and galangin A, 782 corresponding targets were identified. In particular, GSK3β and β-catenin exhibited strong binding activity with the bioactive compounds. Hence, construction of a bioactive component-target network revealed that the mechanism underlying the anti-alopecia mechanism of TGD primarily involved the Wnt/β-catenin signaling pathway. Moreover, C57BL/6J mice exhibited measurable improvements in hair follicle regeneration following treatment with TGD. Additionally, β-catenin and p-GSK3β levels were upregulated, while GSK3β was downregulated in TGD-treated animals and dermal papilla cells compared to control group. These in vivo and in vitro outcomes validated the targets and pathways predicted in the network pharmacology analysis of TGD. This study provides a systematic analysis approach to identify the underlying anti-alopecia mechanisms of TGD, further providing theoretical support for clinical assessment of TGD.